Syriac theology: past and present - Aras, Martina; Rizk, Charbel; Stosch, Klaus von (Beiträge zur Komparativen Theologie, 2023)
This volume takes us back to the roots of Christianity and exemplifies the significance of Syriac Theology for our time. Bringing together articles by scholars from diverse disciplines, this volume aims at a deeper understanding of the legacy, importance, and challenges of Syriac Theology. The articles in the first part of the volume focus on the biblical, exegetical, and christological tradition of the Syriac Orthodox Church. The articles in the second part of the volume explore the dialogical intertextuality between Syriac Christianity, Rabbinic Judaism, and the Quran.